Drug Use Pattern And Cost Analysis Assessment Among Ovarian Cancer Patients In A Tertiary Care Teaching Hospital - A Prospective Observational Study - M, Sanjay.; S, Dilipkumar.; C, Aparna.; Alagappan, Sriram; Vijay, M (Journal of Neonatal Surgery, 2025)
Background: Ovarian cancer ranks as the fifth leading cause of cancer-related deaths among women worldwide. This study aimed to assess drug utilization patterns, adverse drug reactions, and associated costs among ovarian cancer patients in a tertiary care teaching hospital. Methods: This prospective observational study was conducted over six months (December 2023-May 2024) at SRM Medical College Hospital, Tamil Nadu, India. Thirty-two patients with confirmed ovarian cancer receiving chemotherapy were enrolled. Data collection included demographic characteristics, drug utilization patterns, adverse drug reactions and cost analysis across cancer stages. WHO prescribing indicators were applied to evaluate rational drug use. Results: The mean patient age was 53.3±5.6 years, with 56.25% of the patients were from urban region followed by 53.1% of the patients were lower middle class. WHO indicators revealed 6.2 average drugs per prescription with low generic prescribing (17.8%). Vomiting was the most frequently reported ADR (53.1%), followed by nausea (21.8%). Diabetes mellitus was considered as the most common comorbidities 43.75% followed by hypertension with 37.5%. The most commonly used chemotherapeutic agents were Paclitaxel+ carboplatin with 50% followed by Paclitaxel 25% and carboplatin 12.5%. Antiemetics were used commonly with 75% followed by NSAIDS with 60%, PPi with 50%, corticosteroids 59.3% in this study. Conclusions: The study demonstrated adherence to evidence-based chemotherapy protocols. High prevalence of preventable adverse drug reactions (87.5%) indicates opportunities for enhanced patient safety monitoring. Low generic prescribing suggests potential cost optimization. Significant cost variations across stages emphasize the need for stage-specific economic evaluations in treatment planning.